Algorithmic and infrastructural software development for cryo electron tomography - Frosio, T (2023)
Many Cryo Electron Microscopy (cryoEM) software packages have accumulated significant technical debts over the years, resulting in overcomplicated codebases that are costly to maintain and that slow down development. In this thesis, we advocate for the development of open-source cryoEM core libraries as a solution to this debt and with the ultimate goal of improving the developer and user experience.